2016
DOI: 10.4103/0366-6999.195464
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiotherapy Improving Survival Outcomes for Esophageal Carcinoma

Abstract: Background:The effectiveness of neoadjuvant chemoradiotherapy (NCRT) treatment for patients with esophageal carcinoma (EC) remains controversial. The aim of this study was to compare the effect of NCRT followed by surgery (NCRTS) with surgery alone (SA) for EC.Methods:The PubMed, EMBASE, and the Cochrane Library databases were electronically searched up to August 2015 for all the published studies that investigated EC patients receiving either NCRTS or SA, and the reference lists were also manually examined fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Both short-and long-term morbidity and mortality are driven by perioperative complications [3,4]. While many studies have focused on centralization of cancer care, enhanced recovery following surgery and neoadjuvant and adjuvant therapies [5][6][7][8][9][10][11], a key unanswered question is the ideal anastomotic technique.…”
Section: Introductionmentioning
confidence: 99%
“…Both short-and long-term morbidity and mortality are driven by perioperative complications [3,4]. While many studies have focused on centralization of cancer care, enhanced recovery following surgery and neoadjuvant and adjuvant therapies [5][6][7][8][9][10][11], a key unanswered question is the ideal anastomotic technique.…”
Section: Introductionmentioning
confidence: 99%
“…In a meta-analysis by Zhu et al, nine studies which included 1,135 cases (612 received concurrent chemoradiotherapy and 523 received radiotherapy alone) showed that patients who received concurrent chemoradiotherapy, demonstrated significantly higher overall response rate and reduced the risk of persistence and recurrence of disease [14][15][16][17][18].…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%
“…Semi‐mechanical technique was favored by local thoracic surgeons for cervical anastomosis. This gradually gained popularity to be used for intrathoracic anastomosis as well, based on published studies [4–7] and local expertise recommendation. This resulted in a significant reduction in leak rates as demonstrated in our study [1].…”
Section: Circular (N = 85) Semi‐mechanical (N = 74) Overall (N = 159)...mentioning
confidence: 99%